Perfecting the Synergic Effect in Hybrid Multi-agent Systems - Żytniewski, Mariusz (Doskonalenie efektu synergicznego w hybrydowych systemach wieloagentowych, 2010)
The validity of applying hybrid multi-agent system for the purposes of solving a given problem, when compared with other technologies, should stem from their unique features, and should also allow for an additional effect, which may be a result of agents cooperating and connected to distributed processing. The effect obtained by the agents can be called the synergic effect. To achieve and perfect this effect, in the paper a normative knowledge metamodel was proposed as an element of hybrid multi-agent system, designed in OWL ontology language. The first part of the study outlines the concept of hybrid multi-agent systems, as presented in literature, followed by the elaboration upon the term synergic effect. Based on this groundwork, the application of the hybrid multi-agent system was illustrated, a system designed by the author and applied for the purpose of achieving the synergic effect based on the normative knowledge metamodel, employed to support the process of filling out electronic documents. The final part of the study contains conclusions pertaining to the discussed issues.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 114-127
Keywords: hybrid agent; multi-agent systems; knowledge metamodel; synergic effect